Analisis Kontaminasi Bakteri Patogen pada Sayuran yang Dijual di Pasar Tradisional Kota Medan dengan Media EMBA dan SSA - Lumbar Raja, Doan Parulian; Rahmiati, Rahmiati; Susilo, Ferdinand; Nasution, Jamilah (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2024)
Microbial contamination in vegetables often originates from spraying or irrigation with contaminated water. Fertilization using animal manure can also lead to contamination, with bacteria such as Salmonella and E. coli found in vegetables like lettuce. Samples were collected once from each traditional market, repeatedly taken from roadside stalls, inside the market, or from kiosks. Macroscopic colony characteristics on EMBA (Eosin Methylene Blue Agar) and SSA (Salmonella-Shigella Agar) media were observed after incubation, including colony shape, color, structure, and growth size or diameter. EMBA media cultures of E. coli on five vegetable samples from Pasar Melati, Pasar Sei Sikambing, and Pasar Kampung Lalang showed contamination in all five samples. SSA media cultures of Salmonella sp. on five vegetable samples from these markets revealed contamination in one sample. Gram staining of all samples identified Gram-negative bacteria, appearing red in color.